Positive association between epiphytes and competitiveness of the brown algal genus Lobophora against corals - Andreas Eich; Amanda K. Ford; Maggy M. Nugues; Ryan S. McAndrews; Christian Wild; Sebastian C.A. Ferse (PeerJ, 2019)
Observations of coral–algal competition can provide valuable information about the state of coral reef ecosystems. Here, we report contact rates and apparent competition states for six shallow lagoonal reefs in Fiji. A total of 81.4% of examined coral perimeters were found to be in contact with algae, with turf algae (54.7%) and macroalgae of the genus Lobophora (16.8%) representing the most frequently observed contacts. Turf algae competitiveness was low, with 21.8% of coral–turf contacts being won by the algae (i.e. overgrowth or bleaching of coral tissue). In contrast, Lobophora competitiveness against corals was high, with 62.5% of contacts being won by the alga. The presence of epiphytic algae on Lobophora was associated with significantly greater algal competitiveness against corals, with 75.8% and 21.1% of interactions recorded as algal wins in the presence and absence of epiphytes, respectively. Sedimentation rate, herbivorous fish biomass, and coral colony size did not have a significant effect on Lobophora–coral interactions. This research indicates a novel and important role of epiphytes in driving the outcome of coral–algal contacts.